An Evaluative Analysis of Performance Factors and Improvement Strategies in the Cement Deep Mixing (CDM) Project Based on Importance–Performance Analysis (IPA) and the Customer Satisfaction Index (CSI): A Case Study of the ABC Port Project - Andreamara Andreamara; Muhammad Isradi (Eduvest - Journal of Universal Studies, 2026)
The implementation of port infrastructure development often faces challenges related to soft soil conditions that require effective ground improvement methods. Cement Deep Mixing (CDM) has become one of the widely applied techniques for enhancing soil strength and stability; however, its performance is influenced by various technical, managerial, external, and implementation quality factors. This study aimed to evaluate the performance factors affecting the CDM project, identify gaps between the importance and actual performance of these factors, and determine improvement priorities using Importance–Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). A quantitative approach using a survey method was applied to the ABC Port Project, involving 85 respondents consisting of contractors, main contractors, and supervisory consultants directly involved in CDM implementation. Data were collected through questionnaires based on 15 indicators covering technical factors, managerial factors, external conditions, and implementation quality, and were analyzed using IPA and CSI methods. The results showed that the overall CDM project performance was categorized as good, with a CSI value of 87.57%, indicating a very high level of stakeholder satisfaction. However, the analysis revealed a negative performance gap of -0.06 between stakeholder expectations and actual project performance. The highest improvement priorities were related to technical training (M2) and operator and technician competency (M1), indicating the need for stronger human resource development and technical control. This study concludes that the integration of IPA and CSI provides an effective evaluation framework for identifying critical factors and developing targeted strategies to improve CDM project performance.